Cost of institutional harmonization in the ENP countries - Veliko Dimitrov (Center for Social and Economic Research (CASE), 2009)
This paper analyzes the costs of (partial) institutional harmonization with the EU acquis which countries of the former USSR are expected to conduct under their Partnership and Cooperation Agreements with the EU and European Neighborhood Policy Action Plans. The public sector will have to take an effort of the transposition and adaptation of EU norms, as well as ensuring that they are complied with. Yet, the major part of the adjustment costs will fall on the private sector, as enterprises will have to make substantial investments to comply with new product requirements and business practices. In this study we used the method of extrapolation of average costs for CEE countries' harmonization with acquis to estimate the potential harmonization costs for the neighboring countries based on internationally comparative macroeconomic indicators like sectoral and total value added. This involved estimating the EU pre-accession support for the CEE countries by main areas as a percentage of the total or sectoral value added, determining the expected degree of limited harmonization in the ENP countries and estimating coefficients of limited harmonization”, which was subsequently used for adjustment of the estimated cost of full harmonization.
Keywords: F15; P33; 330; Institutional harmonization; European integration; European Neighborhood Policy (ENP); economic integration; market access; Institutionelle Infrastruktur; Institutioneller Wandel; Europäische Integration; EU-Nachbarstaaten; Markteintritt; Kosten; Osteuropa; GUS-Staaten